Election Fraud and Post-Election Conflict: Evidence from the Philippines - Benjamin Crost; Joseph H. Felter; Hani Mansour; Daniel I. Rees (Institute for the Study of Labor (IZA), 2013)
Previous studies have documented a positive association between election fraud and the intensity of civil conflict. It is not clear, however, whether this association is causal or due to unobserved institutional or cultural factors. This paper examines the relationship between election fraud and post-election violence in the 2007 Philippine mayoral elections. Using the density test developed by McCrary (2008), we find evidence that incumbents were able to win tightly contested elections through fraud. In addition, we show that narrow incumbent victories were associated with an increase in post-election casualties, which is consistent with the hypothesis that election fraud causes conflict. We conduct several robustness tests and find no evidence that incumbent victories increased violence for reasons unrelated to fraud.
Keywords: D72; D73; D74; 330; election fraud; conflict